ANALISIS AUDIT OPERASIONAL DALAM MENUNJANG EFISIENSI DAN EFEKTIFITAS PENJUALAN PADA PT. MEGA PRABU MANDIRI - Meirani Betriana (KOLEGIAL, 2021)
Operational audit is an appropriate tool for management to evaluate and assess the level of efficiency and effectiveness of the company's operations. PT. Mega Prabu Mandiri is a company engaged in the sale of medical devices and medical consumables. The purpose of this study is to find out how the operational audit in supporting the efficiency and effectiveness of sales at PT. Mega Prabu Mandiri. The type of research used by the author in this study is descriptive quantitative research because in this study there is a lot of data collecting that is numerical. The data used are primary data and secondary data. Data collection techniques used in this study were observation, interviews, literature study and documentation. The results show that the operational audit has been carried out according to the existing audit stage and shows that the overall sales function has been running efficiently and effectively.